Comparison of exciton-biexciton with bound exciton-biexciton dynamics in GaN: Quantum beats and temperature dependence of the acoustic-phonon interaction - Kyhm, K; Taylor, R; Ryan, J; Aoki, T; Kuwata-Gonokami, M; Beaumont, B; Gibart, P (2001)
The polarization dependence of biexcitonic signals and quantum beats between A-excitons (XA) and A-biexcitons (XAXA) in a high-quality GaN epilayer is measured by spectrally-resolved and time-integrated four-wave mixing. With cross-linear polarised light, mixed beats with two periods are observed: the first beating period corresponds to the energy splitting between XA and XAXA, and agrees well with the calculated XAXA binding energy; while the second beating period corresponds to that between XA and donor bound excitons (D0X). The temperature-dependent homogeneous linewidth shows that the D0X has a larger acoustic phonon coupling coefficient than the XAXA. We also measured the polarization dependent B-biexciton (XBXB) signal. The effective masses for the A- and B-hole were deduced from the binding energy.